Women’s empowerment, extended families and male migration in Nepal: Insights from mixed methods analysis - Meinzen-Dick, Ruth S.; Pereira, Audrey; Pradhan, Rajendra; Doss, Cheryl R. (International Food Policy Research Institute, 2020)
Women’s empowerment is dynamic across the life course, affected not only by age but also by women’s social position within the household. In Nepal, high rates of male outmigration have further compounded household dynamics, although the impact on women’s empowerment is not clear. We use qualitative and quantitative data from Nepal to explore the relationship between women’s social location in the household, caste/ethnicity, husband’s migration status, and women’s empowerment. The study first examines the factors affecting overall empowerment as measured by the Abbreviated Women’s Empowerment in Agriculture Index (A-WEAI), followed by more detailed qualitative and quantitative analysis of how each factor affects individual domains including asset ownership, access to and decisions on credit, control over use of income, group membership, input in productive decisions, and work load. We find that women’s empowerment is strongly associated with caste/ethnic identity and position in the household, but this dynamic interacts with husband’s migration status. Despite patriarchal norms of high caste groups, high caste women are more empowered than others, reflecting the disempowering effects of poverty and social exclusion for low caste and ethnic groups. Daughters-in-law in joint households are more likely to be empowered when their husbands are residents in the household and disempowered when their husbands are migrants, while wives in nuclear households are more likely to be empowered when their husbands are migrants. While qualitative findings indicate daughters-in-law are disempowered compared to their mothers-in-law, especially in time use, the quantitative results do not show significant differences, suggesting that we need to move toward an understanding of agency over time and intensity of work, rather than simply hours worked. Identifying the factors that contribute to disempowerment of women of different social positions has important implications for the design of interventions and programs that seek to improve women’s empowerment.